Space Sciences in Costa Rica - Fernández Rojas, Walter (2000)
In 1992, the Second UN/ESA Workshop on Basic Space Science was held in Costa Rica and Colombia. The Workshop in Costa Rica dealt with the solar system and was instrumen tal in helped to strengthen space science activities in Costa Rica. The following provides a summary of such activities in Costa Rica since 1992.